Diagnóstico: la reforma tributaria y las políticas fiscales necesarias en el Perú. Entrevista a César Luna-Victoria León - Roca Lizarzaburu, Luis Fernando (2013)
The recollection in the Peruvian tax system has been a constant problem over the years, mainly due to the high degree of informality and tax avoidance. The tax reform implemented in 2012 aimed to find a solution to these problems, yet it didn’t embrace themost important issues. It was also heavily criticized for its content, especi by Rule XVI, an anti-avoidance measure allowing Sunat to determine the true nature of the taxable events that weren’t considered in the other cases referred to in the Tax Code, penalizing them when avoidance or fraud occurred.The interviewed lawyer claims that, although the issues that have been addressed in the reform are positive, they have neglected the most important issues –such as public spending, tax procedures and inefficient exemptions– due to political fear, leaving pending again a true tax reform that addresses the most importantissues.